2015
DOI: 10.3332/ecancer.2015.506
|View full text |Cite
|
Sign up to set email alerts
|

The role of trachelectomy in cervical cancer

Abstract: Cervical cancer is one of the most common cancers in women worldwide. Because it often affects women of childbearing age (19–45 years), fertility-sparing surgery is an important issue. The article reviews current viable fertility-sparing options with a special focus on trachelectomy, including vaginal radical trachelectomy, abdominal radical trachelectomy and simple trachelectomy. Neoadjuvant chemotherapy is also discussed. Finally, the decision to proceed with fertility-sparing treatment should be a patient-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…first reported vaginal radical trachelectomy (RT) in 1994, trachelectomy has been increasingly used, and other approaches, such as abdominal, laparoscopic, and robotic procedures have been developed. At present, >900 cases of trachelectomy have been reported in the literature . Since 2010, we have performed abdominal RT (ART) in 28 patients.…”
Section: Introductionmentioning
confidence: 99%
“…first reported vaginal radical trachelectomy (RT) in 1994, trachelectomy has been increasingly used, and other approaches, such as abdominal, laparoscopic, and robotic procedures have been developed. At present, >900 cases of trachelectomy have been reported in the literature . Since 2010, we have performed abdominal RT (ART) in 28 patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The same may be achieved with radical vaginal trachelectomy. 11,19,20 Although associated with lower morbidity compared with type III radical hysterectomy, the morbidity related to parametrial excision is above that of simple hysterectomy. 4,6,28 Management of the parametrium is also important in the treatment of patients requesting fertility preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that only the medial half of the parametrium is removed by vaginal radical trachelectomy, 19,20 and respecting the conclusions of reports on unpredictable parametrial spread, 22Y26 one may question whether this procedure is superior to large cone biopsy with clear resection margins in tumors with a diameter less than 20 mm. 29 Lindsay et al 18 recently reported treatment of 40 patients with stages IA1 to IB1 by repeated LLETZ (large loop excision of the transformation zone) and pelvic lymph node dissection for fertility preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach is not recommended as initial therapy of IB2 tumors (limited to the cervix and having a diameter above 4 cm). [2][3][4][5] For lesions in stage 0 (in situ carcinoma), conization with free margins is sufficient. [2][3][4][5] In stage IA1 (micro-invasion less than 3 mm), the choice will depend on the patient's desire to preserve fertility, and whether there is lymphovascular invasion.…”
Section: Introductionmentioning
confidence: 99%